Population-Based Epidemiology of Heart Failure in a Low-Income Country: The Haiti Cardiovascular Disease Cohort. Issue 2 (6th December 2022) - Kingery, Justin R.; Roberts, Nicholas L.; Lookens Pierre, Jean; Sufra, Rodney; Dade, Eliezer; Rouzier, Vanessa; Malebranche, Rodolphe; Theard, Michel; Goyal, Parag; Pirmohamed, Altaf; Yan, Lily D.; Hee Lee, Myung; et al.
Abstract : Background: Cardiovascular disease disproportionately affects persons living in low- and middle-income countries and heart failure (HF) is thought to be a leading cause. Population-based studies characterizing the epidemiology of HF in these settings are lacking. We describe the age-standardized prevalence, survival, subtypes, risk factors, and 1-year mortality of HF in the population-based Haiti Cardiovascular Disease Cohort. Methods: Participants were recruited using multistage cluster-area random sampling in Port-au-Prince, Haiti. A total of 2981 completed standardized history and exam, laboratory measures, and cardiac imaging. Clinical HF was defined by Framingham criteria. Kaplan-Meier and Cox proportional hazard regression assessed mortality among participants with and without HF; logistic regression identified associated factors. Results: Among all participants, the median age was 40 years (interquartile range, 27–55), and 58.2% were female. Median follow-up was 15.4 months (interquartile range, 9–22). The age-standardized HF prevalence was 3.2% (93/2981 [95% CI, 2.6–3.9]). The average age of participants with HF was 57 years (interquartile range, 45–65), and 67.7% were female. The first significant increase in HF prevalence occurred between 30 to 39 and 40 to 49 years (1.1% versus 3.7%, P =0.003). HF with preserved ejection fraction was the most common HF subtype (71.0%). Age (adjusted odds ratio, 1.36 [1.12–1.66] per 10-year increase), hypertension (2.14 [1.26–3.66]), obesity (3.35 [95% CI, 1.99–5.62]), poverty (2.10 [1.18–3.72]), and renal dysfunction (5.42 [2.94–9.98]) were associated with HF. One-year HF mortality was 6.6% versus 0.8% (hazard ratio, 7.7 [95% CI, 2.9–20.6]; P <0.0001). Conclusions: The age-standardized prevalence of HF in this low-income setting was alarmingly high at 3.2%—5-fold higher than modeling estimates for low- and middle-income countries. Adults with HF were two decades younger and 7.7× more likely to die at 1 year compared with those in the community without HF. Further research characterizing the population burden of HF in low- and middle-income countries can guide resource allocation and development of pragmatic HF prevention and treatment interventions, ultimately reducing global cardiovascular disease health disparities. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03892265.